MHD flow and heat transfer of Cu–water nanofluid in a semi porous channel with stretching walls. (December 2016) - Raza, Jawad; Rohni, Azizah Mohd; Omar, Zurni
Highlights: Heat transfer of MHD copper–water nanofluid in a channel has been studied numerically. Enhancement of solid volume friction φ from 0 to 0.9 increases the velocity profile f ′( η ) from lower wall to the center of the channel and afterwards decreases. Stretching Reynolds number R  > 0 increases the velocity profile prior to the half of channel and decrease gradually after. Solid volume fraction φ decreases the skin friction f ″(−1) which implies that fluid near the lower wall is under the high influence of slip effect which leads to increase the velocity of the fluid. Rising the strength of Prandtl number Pr increases heat transfer rate − θ ′(−1). Abstract: This paper deals with heat transfer analysis on MHD nanofluids in a porous channel with stretching walls. An incompressible Copper (Cu)–water nanofluid is filled in the porous channel. The governing partial differential equations are first transformed into ordinary differential equations by using suitable similarity transformation. The resulting nonlinear ordinary differential equations are then solved numerically by using shooting method. It is found that the different values of nanoparticle volume fraction, Reynolds number, magnetic field and Prandtl number affects the profiles of velocity, temperature, skin friction and heat transfer.